2020
DOI: 10.1101/2020.04.27.063859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of 1’-Ribose Cyano Substitution for Remdesivir to Effectively Inhibit Nucleotide Addition and Proofreading in SARS-CoV-2 Viral RNA Replication

Abstract: COVID-19 has recently caused a global health crisis and an effective interventional therapy is urgently needed. SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) provides a promising but challenging drug target due to its intrinsic proofreading exoribonuclease (ExoN) function. Nucleoside triphosphate (NTP) analogues added to the growing RNA chain should supposedly terminate viral RNA replication, but ExoN can cleave the incorporated compounds and counteract their efficacy. Remdesivir targeting SARS-CoV-2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 72 publications
2
11
0
Order By: Relevance
“…Regarding the mechanism of action, Li’s group highlighted that GS-5734 can bind to the RNA-binding channel of the SARS-CoV-2 RNA-dependent RNA polymerase ( Wu et al., 2020 ) ( Figure 5 ). The 1’-ribose CN substitution observed in GS-5734 plays an important role in inhibiting the viral RNA replication of SARS-CoV-2 ( Zhang et al., 2020 ).…”
Section: Promising Natural Product-inspired Agents For Treating Sars-mentioning
confidence: 99%
“…Regarding the mechanism of action, Li’s group highlighted that GS-5734 can bind to the RNA-binding channel of the SARS-CoV-2 RNA-dependent RNA polymerase ( Wu et al., 2020 ) ( Figure 5 ). The 1’-ribose CN substitution observed in GS-5734 plays an important role in inhibiting the viral RNA replication of SARS-CoV-2 ( Zhang et al., 2020 ).…”
Section: Promising Natural Product-inspired Agents For Treating Sars-mentioning
confidence: 99%
“…Choy et al [ 140 ] reported the efficiency of Remdesivir and three other drugs against COVID-19 in Vero E6 cells, with EC 50 values of 23.15 µM (Remdesivir), 26.63 µM (Lopinavir), 2.55 µM (Homorringtonine) and 0.46 µM (Emetine), respectively. Zhang et al [ 141 ] found that the 1′-cyano group of Remdesivir has dual roles in inhibition of nucleotide addition and proofreading. Pruijssers et al [ 142 ] reported that Remdesivir potently inhibits SARS-CoV-2 replication in human lung cells and primary human airway epithelial cultures (EC 50 = 0.01 µM), in Vero E6 cells (EC 50 = 1.65 µM), respectively.…”
Section: Remdesivirmentioning
confidence: 99%
“…[207][208] Yin et al reported a cryo-electron microscopy structure of the SARS-CoV-2 RdRp in complex with a 50-base template-primer RNA and remdesivir (99) at 2.5-angstrom resolution (PDB 7BV2) (Figure 12A-B). [209] The complex structure indicated that the partial double-stranded RNA template is placed into the central channel of the RdRp, where a molecule 99 is covalently assimilated into the primer strand at the first replicated base pair and terminates chain elongation. Later on, Bravo et al reported 3.9-Å-resolution cryo-EM reconstruction of a remdesivir-stalled RNA-dependent RNA polymerase complex (PDB 7 L1F) (Figure 12C).…”
Section: Pharmacological Relevance Of Remdesivir (Gs-5734) (99) In Sars-cov-2mentioning
confidence: 99%